2011
DOI: 10.1590/s0102-695x2011005000048
|View full text |Cite
|
Sign up to set email alerts
|

Anti-snake venom effect of secodolastane diterpenes isolated from Brazilian marine brown alga Canistrocarpus cervicornis against Lachesis muta venom

Abstract: Abstract:The effect of a Brazilian algae extract and also a mixture of two secodolastane diterpenes (linearol/isolinearol) that were isolated from the marine brown alga Canistrocarpus cervicornis were evaluated against biological activities of Lachesis muta snake venom. In vitro assays showed that the crude extract and the diterpenes were able to inhibit the clotting and proteolytic activity induced by L. muta crude venom, but not the hemolytic activity. However, only the diterpenes inhibited the hemolysis cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The diterpenes (87 µg/g) did not inhibit edematogenic activity of B. jararaca venom (at 2 µg/g, data not shown); and thus, would not prevent inflammation induced by snake bites. On the other hand, in our previous work, this mixture of diterpenes inhibited hemolysis and edema induced by a PLA 2 isolated from L. muta [21]. Despite the similarity in composition between the B. jararaca and L. muta venoms, the presence of specific components in each venom may explain the different inhibitory profiles of the diterpenes.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The diterpenes (87 µg/g) did not inhibit edematogenic activity of B. jararaca venom (at 2 µg/g, data not shown); and thus, would not prevent inflammation induced by snake bites. On the other hand, in our previous work, this mixture of diterpenes inhibited hemolysis and edema induced by a PLA 2 isolated from L. muta [21]. Despite the similarity in composition between the B. jararaca and L. muta venoms, the presence of specific components in each venom may explain the different inhibitory profiles of the diterpenes.…”
Section: Resultsmentioning
confidence: 76%
“…In Brazil, the brown marine algae are the most widely studied, with more than 300 diterpenes isolated from at least 35 species all over the world [19]. Although some biological activities have been studied [21,25,26,27], the potential of brown seaweeds to neutralize the toxic effects of snake venoms has not been widely investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have been focused on the search for inhibitors of snake venoms from a variety of sources, be they natural or synthetic [31, 32]. Suramin [3335] and benzoyl phenyl benzoate [36] are synthetic molecules able to inhibit myotoxicity, clotting, and phospholipase A 2 and hyaluronidase activities of snake venoms from different families.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed the ability of dolastane and secodolastane diterpenes isolated from C. cervicornis marine brown alga to inhibit hemolytic, proteolytic, hemorrhagic and clotting activities of L. muta venom (Moura et al, 2010;Domingos et al, 2011). We have now evaluated the ability of S. schröederi algal extracts prepared with solvents of increasing polarities (n-Hexane, dichloromethane, ethyl acetate) to neutralize the hemolytic, proteolytic, hemorrhagic and clotting activities of crude L. muta venom.…”
Section: Resultsmentioning
confidence: 99%